CrkL meditates CCL20/CCR6-induced EMT in gastric cancer. Issue 2 (December 2015) - Han, Gang; Wu, Dawei; Yang, Yongan; Li, Zhiyun; Zhang, Jiapin; Li, Chengjun
Highlights: CCR6 and CrkL expressed in gastric cancer tissues and cell lines. CCR6 and CrkL expression predicted poor prognosis of gastric cancer. Knockdown of CrkL abrogated CCL20-induced Erk1/2 signaling and EMT. Knockdown of CrkL affected CCL20-induced MGC803 migration and invasion. Abstract: Background: In recent years, Crk-like adapter protein (CrkL) has been identified as a key regulator in the epithelial-to-mesenchymal transition (EMT). However, the molecular mechanisms underlying the CC chemokine receptor 6 (CCR6) and chemokine (C–C motif) ligand 20 (CCL20)-induced EMT in gastric cancer are still unclear. Methods: We conducted the immunohistochemistry and immunoblotting to detect the expression of CCR6 and CrkL in 90 cases of gastric cancer tissues and five kinds of cell lines. And then, gastric cancer cells were subjected to small interfering RNA (siRNA) treatment and in vitro assay. Results: Both CCR6 and CrkL were aberrantly expressed in gastric cancer specimens and closely correlated with differentiation of cell lines. The expression of CCR6 and CrkL was also significantly associated with metastasis, stage, and poor prognosis of gastric cancer. In addition, we validated CCL20 activated the expression of p-CrkL, p-Erk1/2, p-Akt, vimentin, N-cadherin and MMP2 in MGC803 cells in a dose-dependent manner. However, si-CrkL abrogated the CCL20-induced p-Erk1/2, vimentin, N-cadherin and MMP2 expression. Most importantly, the knockdown of CrkL decreased migration and invasion of MGC803 cells. Conclusions: CrkL mediates CCL20/CCR6-induced EMT via Akt pathway, instead of Erk1/2 pathway in development of gastric cancer, which indicated CCL20/CCR6–CrkL–Erk1/2–EMT pathway may be targeted to antagonize the progression of gastric cancer.